Adaptative potential of the Lactococcus lactis IL594 strain encoded in its 7 plasmids. - Roman K Górecki; Anna Koryszewska-Bagińska; Marcin Gołębiewski; Joanna Żylińska; Marcin Grynberg; Jacek K Bardowski (PLoS ONE, 2011)
The extrachromosomal gene pool plays a significant role both in evolution and in the environmental adaptation of bacteria. The L. lactis subsp. lactis IL594 strain contains seven plasmids, named pIL1 to pIL7, and is the parental strain of the plasmid-free L. lactis IL1403, which is one of the best characterized lactococcal strains of LAB. Complete nucleotide sequences of pIL1 (6,382 bp), pIL2 (8,277 bp), pIL3 (19,244 bp), pIL4 (48,979), pIL5 (23,395), pIL6 (28,435 bp) and pIL7 (28,546) were established and deposited in the generally accessible database (GeneBank). Nine highly homologous repB-containing replicons, belonging to the lactococcal theta-type replicons, have been identified on the seven plasmids. Moreover, a putative region involved in conjugative plasmid mobilization was found on four plasmids, through identification of the presence of mob genes and/or oriT sequences. Detailed bioinformatic analysis of the plasmid nucleotide sequences provided new insight into the repertoire of plasmid-encoded functions in L. lactis, and indicated that plasmid genes from IL594 strain can be important for L. lactis adaptation to specific environmental conditions (e.g. genes coding for proteins involved in DNA repair or cold shock response) as well as for technological processes (e.g. genes encoding citrate and lactose utilization, oligopeptide transport, restriction-modification system). Moreover, global gene analysis indicated cooperation between plasmid- and chromosome-encoded metabolic pathways.